Is guanxi important in a buyer-supplier relationship? Case of Chinese logistics industry. Issue 1 (19th December 2019) - Butt, Atif Saleem; Shah, Syed Hamad Hassan; Sheikh, Abdullah Zafar
Abstract : Purpose: The purpose of this paper is to unveil negative outcomes associated with an absence of guanxi in a buyer–supplier relationship in Chinese logistics industry. Design/methodology/approach: This study uses a case study methodology using 16 semi-structured interviews with managers engaged in the process of buying and selling logistics services in China. Findings: Based on the qualitative interviews, managers experience lack of trust, lack of communication flow and reduced business volume when guanxi is absent in a buyer–supplier relationship in the Chinese logistics industry. Research limitations/implications: This study has some limitations. First, the results of this study are not generalizable to a broader population. Second, this study explores behavioral patterns with respect to Chinese business culture only. Practical implications: Firms can use the findings from this study to understand the consequence they can face when guanxi is absent in a buyer–supplier relationship. Originality/value: This study attempts to offer a balanced perspective on the role of guanxi in a buyer–supplier relationship, particularly in the Chinese logistics industry, by considering how an absence of guanxi generates negative outcomes for firms.